Hubungan Tingkat Pengetahuan dan Sikap Terkait Diabetes Melitus dengan Kadar Glukosa Darah Sewaktu (GDS) Lansia di Wilayah Puskesmas Tanggulangin - Selfia, Sona (Jurnal Ilmiah Universitas Batanghari Jambi, 2024)
Diabetes mellitus (DM) was a metabolic disease characterized by an increase in blood glucose levels accompanied by a decrease in carbohydrate, protein and fat metabolism. The elderly group (elderly) was the group most at risk of developing dm because this group was a population that was susceptible to carbohydrate metabolism disorders which could lead to diabetes mellitus. This studied aims to analyze the relationship between the leveled of knowledge and attitudes regarding dm on the blood sugar levels of the elderly. This researched used an observational studied with a crossed sectional approached. The population in this studied was members of the elderly posyandu in the working area of the tanggulangin community health center used a random sampling technique of 88 respondents. Data collection used knowledge questionnaires and attitude questionnaires. Data was analyzed used univariate analysis and bivariate analysis (chi square test). The results of the analysis showed that the leveled of knowledge (p=0,011) and attitudes of the elderly (p=0,008) regarding diabetes mellitus showed a significant relationship (p<0,05)